Gestão de custos como instrumento de governança pública: um modelo de custeio para os hospitais públicos do Paraná - Blanski, Márcia Beatriz Schneider (2015)
Cost management brings about several benefits to any type of organization, such as the certainty that resources are well managed, but it is not much used by the public hospital sector, what is a paradox seeing that hospital management is complex and public health faces an under-financing situation. Based on the aforementioned facts, the present study aims at answering the following question: What is the contribution of costing models to public governance in the State of Paraná public hospitals? So, the study objective is to propose a costing management model addressed to improve health strategy control, transparency, budget and planning actions in public hospitals directly managed by the State of Paraná. Since the hospital sector is complex, our study is highly relevant as a helping tool to: investment decision-making processes, changes of healthcare profile, use of spare capacity and service improvement, among others. Considering the universal rights ensured by the Brazilian Federal Constitution, the country public health system needs to show maximum efficiency. In addition to hospital complexity, the sector increased costs are justified by the change of demographic and epidemiological profiles, Brazilian population aging, chronic disease growth, increased technological evolution and development. The research/action is based on the results of similar researches addressed to analyze the application of costing models addressed to hospital organization, as well as on the empiric analysis of data existing in two hospitals selected by the study. By applying the theoretical and empiric costing absorption methodology, our study provides elements to help understanding the problems involved in the costing model development. Result assessment is an important tool which permits Hospital and the State Health Department managers to deal with the sector challenges and difficulties more easily, since it helps lessen the restrictions imposed to public hospital management, financing and operation.